(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
Low iron levels in bone marrow and blood plasma cause reduced hemoglobin synthesis, which hinders the trophic development of organs and tissues. This condition is known as iron deficiency anemia.